Efficacy of niclosamide and ivermectin suspension preparations in sheep parasitoses (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This study aimed to examine the efficiency of newly formulated drugs based on mechanochemical modification of two widely used anthelmintic substancesin suspension formulations against the main classes of helminths and parasitic arthropods. Materials and Methods: Solid-phase co-grinding of two substances, i.e., ivermectin (IM) and niclosamide (NS), with licorice extract and sodium succinate was performed in liquid-phase processing to obtain suspension formulations. Drug preparations were administered to the sheep of the experimental groups (5 experimental groups of 8 heads) with different concentrations of active substances, i.e., 3.0, 5.0, and 10.0 mg/kg of body weight (BW) NS and 0.2-mg/kg BW IM. Aqueous suspensions of the original substances in dosages of 0.2-mg/kg BW IM, 10.0-mg/kg NS, and placebo were included as controls. Efficacy of the formulations against gastrointestinal strongyles, Trichuris spp., Moniezia spp., and nasal bot larvae (Oestrus ovis) was assessed in naturally infected sheep by the number of surviving adult parasites post-treatment in the gastrointestinal tract, nasal passages, and sinuses. Results: Formulated suspensions showed an increased solubility of 5.5–13.1 times compared to the original substances. Treatment of sheep with the SusIN-10 drug containing 0.2-mg/kg BW IM and 10.0-mg/kg NS showed 100% efficiency against gastrointestinal strongyles, Moniezia, and nasal bot larvae. Formulations containing 0.2-mg/kg BW IM and 3.0- and 0.5-mg/kg NS could eliminate all of the Trichuris worms. Administration of original substances of IM and NS with recommended dosages did not result in the adult parasites’ complete elimination. Conclusion: Modification of the anthelmintic substances through mechanochemical methods made it possible to create formulations with a targeted spectrum of action, significantly higher water solubility, and optimal parasiticidal activity.J. Adv. Vet. Anim. Res., 11(4): 1122–1129, December 2024http://doi.org/10.5455/javar.2024.k863